The effects of Prostaglandin J2 metabolite on selected apoptotic signaling molecules in UeLa cells - Rabail, Nasir Aziz (Universiti Sains Malaysia, 2006)
Cancer of the cervix is one of the most rapidly increasing malignancies throughout the world and rated as the second most common cancer in Malaysian women. A ligand-dependent nuclear receptor, peroxisome proliferator-activated receptor gamma (PPARy) has been reported to be expressed in various cancer cells including breast, prostate, co lorecta I and cervical cance:r. Recently, down regulation of PPARy has been reported in human cervical carcinoma. Investigations have demonstrated that activation of PPARy is linked to growth inhibition of various cancers by induction of necrosis, apoptosis and growth arrest. This study aims to identify the effect of selective PPARy ligand, 15-Deoxyprostaglandin J2 (15d-PGJ2) on selected apoptotic molecules in the cervical cancer cell line, HeLa. HeLa cells were cultured and treated with an ECso dose of 15dPGJ2. These cells were harvested at every sixth hour of incubation period starting from 0 - 72 hours. Western bJot analysis revealed that Aid expression (anti apoptotic) was down regulated, while caspase 9 and caspase 3· (both are pro apoptotic) expression was up regulated. This finding provides significant evidence on the mechanism of apoptotic action of PPARy ligand that is potentially useful as a chemotherapeutic agent.